Interv'iu s Margaret Tetcher . Interv'iu s Margaret Tetcher . Interview with Margaret Thatcher . Интервью с Маргарет Тэтчер - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Journalists interview Great Britain's Prime Minister, Margaret Thatcher, after her meeting with Mikhail Gorbachev and other Soviet leaders. Featured in the program: Thatcher, Margaret (British Prime Minister) Журналисты интересуются выводами Тэтчер по окончанию встреч с Горбачевым и советскими руководителями. В программе участвуют: Тэтчер, Маргарет (Премьер-министр Великобритании)